A Aplicabilidade da Pesquisa-ação na Educação Musical - Albino, Cesar [UNESP]; Albano de Lima, Sonia Regina [UNESP] (Univ Federal Goias, 2009)
Action-research is a model of scientific investigation which is not widely used in musical teaching, even considering its relevant application in the social sciences. David Tripp (2005) classifies it as a type of action-investigation which is used to define any process that follows a cycle where the practice is improved by the systematic oscillation from acting in the field of practice to investigating into it. With the approval by the Brazilian National Congress of Law 17,769, on August 18, 2008, and with the supplementary legislation, we understand that its use in the musical education would be beneficial. This justification has motivated the writing of this article, which approached the characteristics, functions and usefulness of the action-research. The consulted authors were, among others, D. Tripp, M. Thiollent, Maria A. Franco, G. Morceau, and Maria G. de Miranda. Two examples of Master's dissertations which adopted this type of research were mentioned.
Applicability of action-research in music education
Keywords: Action-research; Musical teaching; Characteristics